Serological evidence of West Nile virus infection in archived swine samples from Peninsular Malaysia - Mohammed, Mohammed Nma; Abd Rahaman, Nor Yasmin; Mohd Adzahan, Noraniza; Ramanoon, Siti Zubaidah; Arshad, Siti Suri; Bande, Faruku; Mohammed, Hussni O. (Korean Society of Veterinary Science,Daehan Suui Hakoe, 2021)
West Nile virus (WNV), a neurotropic arbovirus, has been detected in mosquitos, birds, wildlife, horses, and humans in Malaysia, but limited information is available on WNV infection in Malaysian pigs. We tested 80 archived swine serum samples for the presence of WNV antibody and West Nile (WN) viral RNA using ID Screen West Nile Competition Multi-species enzyme-linked immunosorbent assay kits and WNV-specific primers in reverse transcription polymerase chain reaction assays, respectively. A WNV seroprevalence of 62.5% (50/80) at 95% confidence interval (51.6%–72.3%) was recorded, with a significantly higher seroprevalence among young pigs (weaner and grower) and pigs from south Malaysia. One sample was positive for Japanese encephalitis virus antibodies; WN viral RNA was not detected in any of the serum samples.